Weaning from venous-arterial extracorporeal membrane oxygenation: The hemodynamic and clinical aspects of flow challenge test - Luo, Jing-chao; Zhang, Yi-jie; Hou, Jun-yi; Luo, Ming-hao; Liu, Kai; Tu, Guo-wei; Luo, Zhe (Frontiers in Medicine, 2022)
The cardiac function reserve is crucial for the successful weaning of VA-ECMO. During the VA-ECMO weaning phase, the gradual reduction in pump flow converts the blood flow originally driven by the pump to native cardiac output and also transforms afterload (caused by retrograde flow) into ventricular preload, thus introducing a “flow challenge” to the native heart. In this perspective, we propose to use this flow challenge as a test to simulate the preload-to-afterload conversion to assess cardiac functional reserve quantitatively. With this short article we offer the hemodynamic and clinical aspects regarding the flow challenge test.